2007
DOI: 10.1136/hrt.2006.112771
|View full text |Cite
|
Sign up to set email alerts
|

64-Slice CT coronary angiography in patients with non-ST elevation acute coronary syndrome

Abstract: 64-slice CTCA has a high sensitivity to detect significant coronary stenoses, and is reliable to exclude the presence of significant coronary artery disease in patients who present with a non-ST elevation ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 23 publications
4
46
0
7
Order By: Relevance
“…Sensitivity for significant stenosis in severely calcified coronary segments remained high (93% to 100%) for 64-slice MDCT (8,12,17). Unfortunately, specificity for significant stenosis was variable (67% to 92%) in the setting of severe calcification, suggesting that calcification-associated artefact with 64-slice MDCT leads predominantly to overestimation of lesion obstruction (8,12,17).…”
Section: Assessment Of Significant Cad Using Mdctmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity for significant stenosis in severely calcified coronary segments remained high (93% to 100%) for 64-slice MDCT (8,12,17). Unfortunately, specificity for significant stenosis was variable (67% to 92%) in the setting of severe calcification, suggesting that calcification-associated artefact with 64-slice MDCT leads predominantly to overestimation of lesion obstruction (8,12,17).…”
Section: Assessment Of Significant Cad Using Mdctmentioning
confidence: 99%
“…Currently, 15 studies have examined 64-slice technology for the evaluation of suspected CAD (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) (Figure 2). In these studies, 64-slice MDCT was able to assess 97% of all coronary artery segments visualized by both CCA and MDCT (Table 1), which is approximately 5% more than previous 16-slice technology.…”
Section: Assessment Of Significant Cad Using Mdctmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13] Although clinical algorithms can successfully risk stratify patients, they have not typically been considered useful in identifying a group of patients with a 30-day 1% risk for an adverse event who can safely be discharged from the ED. [2][3][4][5][6][7][8][9][10][11][12][13][14] Coronary computerized tomographic angiography (CTA) has been shown to have excellent diagnostic accuracy when compared to cardiac catheterization [15][16][17][18][19][20][21] and appears to perform as well as myocardial perfusion imaging in identifying patients at low risk for cardiovascular events. [22][23][24][25][26] Observational studies of coronary CTA have found that patients with normal coronary CTA results are at low risk for adverse events over 1-2 years; however, these studies either were small or involved patients who had other standard assessments to aid in clinical management.…”
mentioning
confidence: 99%
“…Sixty-four-slice computed tomography (CT) has been shown to be a reliable noninvasive tool to document or rule out significant coronary artery lesions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In particular, the high negative predictive value (NPV) of CT coronary angiography (CTCA), demonstrated in all studies (1-10), has been suggested to obviate the need for invasive coronary angiography (ICA) in patients whose symptoms or abnormal stress test results require ruling out the presence of coronary artery disease (CAD) (11).…”
mentioning
confidence: 99%